PERTANGGUNGJAWABAN PERDATA TERHADAP ARTIFICIAL INTELLIGENCE YANG MENIMBULKAN KERUGIAN MENURUT HUKUM DI INDONESIA - Yolanda Simbolon (Veritas et Justitia, 2023)
Artificial Intelligence ranging from the simple ones to the advanced forms is developed by various countries, including Indonesia. It is then inavoidable that all these types of Artificial Intelligence might produce errors and causing loss to the user. Unfortunately, at present there is no law in Indonesia explicitly regulates the legal protection for users who encounter material and immaterial losses due to output errors made by Artificial Intelligence. This research is done to contribute in the field of private law with a normative and descriptive approaches. It is found that dynamic and open regulation is needed to anticipate and deal with any future risks. As a conclusion, as there is no legislation that specifically regulates the responsibility of material and immaterial losses caused by Artificial Intelligence, hence at present we can only rely on Article 1367 of the Burgerlijk Wetboek known as strict liability. Artificial Intelligence can be considered as an intangible property, therefore the person who oversees the use of Artificial Intelligence has a responsibility for the losses caused in the course of the use of Artificial Intelligence.